Organic Solar Cells Using a High‐Molecular‐Weight Benzodithiophene–Benzothiadiazole Copolymer with an Efficiency of 9.4%. (27th November 2014) - Subbiah, Jegadesan; Purushothaman, Balaji; Chen, Ming; Qin, Tianshi; Gao, Mei; Vak, Doojin; Scholes, Fiona H.; Chen, Xiwen; Watkins, Scott E.; Wilson, Gerard J.; Holmes, Andrew B.; Wong, Wallace W. H.; et al.
<x xml:space="preserve">Abstract</x> A high molecular weight donor–acceptor conjugated polymer is synthesized using the Suzuki polycondensation method. Using this polymer, a single‐junction bulk‐heterojunction solar cell is fabricated giving a power conversion efficiency of 9.4% using a fullerene‐modified ZnO interlayer at the cathode contact. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>